The Intentions of Health Personnel Using UTAUT-Based Electronic Medical Records (Unified Theory of Acceptance and Use of Technology) - Faida, Eka Wilda; Sutha, Diah Wijayanti (Indonesian Journal Publisher, 2024)
The government's efforts as a form of supporting the Sustainable Development Goals (SDGs) in point 3 regarding health and welfare, the Indonesian government. By using good information technology, it is hoped that good quality health services will also be achieved. The existing conditions at the Jemur Sari Islamic Hospital (RSI) Surabaya show that there are still incomplete Subject, Object, Assessment, Plan (SOAP) components in EMR in 2022. The aim of this research is to review the use of UTAUT-based EMR. This type of observational research uses a cross sectional design. The research sample was taken by total sampling from the entire population, namely 45 officers at Jemur Sari Hospital, Surabaya. Data analysis using frequency descriptives. The research results show that average job fit on performance expectancy 3,48, perceive ease of use on effort expectancy 3,47, subjective norm on social influence 3,43, compatibility on facilitating conditions 3,53 and persuasiveness on behavioral intention 3,50. The results in the very good category and social factors are in the good category. The conclusion of this research is that it needs to be further improved in the aspects of extrinsic motivation, perceived behavioral control, social factors, improvements in complexity and enthusiasm.